Experiments on Reducing Negative Skin Friction of Piles. (3rd December 2019) - Feng, Zhongju; Hu, Haibo; Zhao, Ruixin; He, Jingbin; Dong, Yunxiu; Feng, Kai; Zhao, Yawan; Chen, Huiyun
Abstract : The objective of this study was to investigate the effect of different moisture contents of clay (13%, 15%, 17%, 19%, and 21%) and different coatings on the ability to reduce negative skin friction during a large-scale shear test. Four coating treatments of the concrete surface were investigated, i.e., no treatment, coating with a paraffin-oil mixture, coating with a polymer nanomaterial, and coating with paint. The results showed that when the moisture content of the clay was slightly larger than that of the plastic limit, the ability to reduce negative skin friction was the best, and the performance was similar for the paraffin-oil mixture, the polymer nanomaterial, and the paint. When the moisture content of the clay was lower than that of the plastic limit, the paraffin-oil mixture provided the best performance. The position of the neutral point can be determined by different methods, and the negative skin friction of piles should be reduced by applying coatings that are most suitable to different conditions.